The Analysis of Factors Influencing Work Stress in Educational Personnel at State Universities: Analisis Faktor Yang Mempengaruhi Stres Kerja Pada Tenaga Kependidikan Perguruan Tinggi Negeri - Edy Wahyono; Ramadhan Maruta Pradana; Andi Rezza Kusuma Joesoef Maulana; Umarul Faroq (Prodi Pendidikan Agama Islam FTIK IAIN Palopo, 2025)
This study aims to analyze the level of work stress, the factors that influence it, and identify the dominant factors that influence work stress in educational staff X. This faculty is relatively new with demands for HR efficiency in handling the complexity of workloads and organizations that have the potential to cause stress. Methodology This study uses quantitative descriptive using saturated sampling involving 29 educational staff of Faculty X as respondents. Data were collected through questionnaires based on the theory of Lazarus and Folkman (1984) and analyzed using descriptive analysis, Pearson correlation, and multiple linear regression. The results of the descriptive analysis indicate that most staff have moderate levels of work stress. Regression analysis found that two main factors that have a significant influence are Primary Assessment (perception of workload) and Social Support. The Social Support factor was identified as the most dominant factor influencing the level of work stress, with a strong negative relationship (B = -0.752; p = 0.002), indicating that the higher the social support, the lower the level of work stress. Conversely, Primary Assessment has a positive effect, where increasing the perception of workload increases stress. Practical implications emphasize the need to focus on strengthening social support systems, leadership-staff communication, and effective workload management to create a supportive work environment that promotes employee well-being.